A high-quality chromosome-level genome assembly of Antiaris toxicaria - Weicheng Huang; Jiaxin Xiang; Yamei Ding; Wanzhen Liu; Ni Fang; Yongmei Xiong; Seping Dai; Hui Yu (BMC Genomic Data)
Abstract Objectives Antiaris toxicaria is a tall tree belonging to the Moraceae family, known for its medicinal value. Its latex contains various cardiac glycosides, which hold significant research and potential application value. However, the lack of genomic resources for A. toxicaria currently hinders molecular genetic studies on its medicinal components. For its effective conservation and elucidation of the distinctive genetic traits of and medical components, we present its chromosome-level genome assembly. Data description Here, we assembled two haplotypes of A. toxicaria, including a 671.73-Mb HapA subgenome containing 27,213 genes and a 666.41-Mb HapB subgenome containing 28,840 genes. Their contig N50 sizes were 90.18 and 90.29 Mb, respectively. The transposable elements represented 61.15% and 64.13% of the total assembled genome in HapA and HapB subgenome, respectively. A total of 27,213 and 28,840 genes were predicted in the two haplotypes. Hopefully, this chromosome-level genome of A. toxicaria will provide a valuable resource to enhance understanding of the biosynthesis of medicinal compounds.